Marine Debris Generation in The Cimandiri Estuarine Area River Flow, Palabuhanratu Bay: Timbulan Sampah Laut Di Daerah Muara Aliran Sungai Cimandiri, Teluk Palabuhanratu - Indri Yani Zaini; Sigid Hariyadi; Taryono (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2022)
The beach is a location of the largest marine debris discovery because of the dynamics of the oceanography which is in direct contact with the land. Not a few beaches are close to the river and are vulnerable to being affected by domestic or household waste that comes from river flows. Palabuhanratu Bay is one of the tourist areas affected by waste input from various community activities on the land. Thus, it is necessary to discuss the identification and analysis of marine debris pollution in Palabuhanratu Bay, especially those from the Cimandiri River. The purpose of this study was to identify the distribution of waste types based on full moon and new moon conditions in Palabuhanratu Bay, Sukabumi, West Java. Sampling of marine debris data uses the line transect method and then garbage collection is carried out when the waste has accumulated. The collected waste is then cleaned, sorted and collected by category and then recorded on the marine debris sampling sheet. The types of waste observed included seven categories. The results showed that the waste generation during the full moon was 927 items, while in the new moon was 2,099 items. The density of waste at the research site was 1.85 items/m² (full moon) and 4.20 items/m² (new moon). The types of waste that are mostly found during the full moon and new moon are plastic waste in the amount of 16.87 to 47.08% and other types of waste (wood) is 38.75 to 73.29%.